2016
DOI: 10.18869/acadpub.jafm.68.228.24332
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Drag Reduction Performance of Rigid Polymer–Carbon Nanotubes Complexes

Abstract: Transporting liquids in commercial Pipeline is very expensive due to cost incurred in the installation of pumping stations. This cost can be reduced by polymeric additives. However, these polymeric additives degrade over time as a result of mechanical stress the fluids are subjected to. Previous efforts to address these problems have not been successful. It is thus inevitable to find alternative means of reducing the frictional drag in fluid flow. In this present work, the experimental study of rigid polymer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…However, going by what has happened in the Figure, it is clear that the complex performed best compared to every other additives. Interestingly, looking at all the DRAs which were prepared at different concentrations, it was observed that the PDDAC of about 200ppm showed least performance while XG of 50ppm was able to perform better than the PDDAC , this is a confirmation of the report presented by Edward that the Rigid polymers are very effective and only a little concentration has great impact on drag reduction [15] In addition the XG of about 700ppm was able to reduce drag more than the PDDAC of 1000ppm which further confirms the report by [14]. The mechanical resistance of these polymeric additives is low due to its very high molecular weight and long chain and as such degrades over critical shear stress, surfactants ability of self repairing after degradation resulted into combining these, surfactants when added to polymers generates threadlike micelles that are self repairing after they might have degraded, addition of the surfactant leads to greater drag reduction.…”
Section: Rotational Disk Apparatus Effect Of Shear Rate (Rotationsupporting
confidence: 65%
See 1 more Smart Citation
“…However, going by what has happened in the Figure, it is clear that the complex performed best compared to every other additives. Interestingly, looking at all the DRAs which were prepared at different concentrations, it was observed that the PDDAC of about 200ppm showed least performance while XG of 50ppm was able to perform better than the PDDAC , this is a confirmation of the report presented by Edward that the Rigid polymers are very effective and only a little concentration has great impact on drag reduction [15] In addition the XG of about 700ppm was able to reduce drag more than the PDDAC of 1000ppm which further confirms the report by [14]. The mechanical resistance of these polymeric additives is low due to its very high molecular weight and long chain and as such degrades over critical shear stress, surfactants ability of self repairing after degradation resulted into combining these, surfactants when added to polymers generates threadlike micelles that are self repairing after they might have degraded, addition of the surfactant leads to greater drag reduction.…”
Section: Rotational Disk Apparatus Effect Of Shear Rate (Rotationsupporting
confidence: 65%
“…The mechanical resistance of these polymeric additives is low due to its very high molecular weight and long chain and as such degrades over critical shear stress, surfactants ability of self repairing after degradation resulted into combining these, surfactants when added to polymers generates threadlike micelles that are self repairing after they might have degraded, addition of the surfactant leads to greater drag reduction. However, comparing the XG at 700 ppm to the complex, it could be seen that the complex showed greater performance and this could be as a result of the synergy offered by these individual additives [15,16]. One of the reasons behind the development of complexes is to enhance polymer drag reduction abilities and resistance to mechanical stability.…”
Section: Rotational Disk Apparatus Effect Of Shear Rate (Rotationmentioning
confidence: 99%
“…Each type of drag-reducing agent (DRA) has diverse techniques to decrease the drag within the pipeline system. Although still efficiently founded, drag-reducing agents are thought to work in several ways like turbulence repression, expansion of laminar domain limit to maximum Reynolds Number, near wall flow modulation, and friction detraction in totally advanced turbulence flow [3][4][5]. The aim of the present review is to survey the studies relating to the methods of reducing the drag in the oil pipelines and review the materials that are used as efficient drag reducers.…”
Section: Introductionmentioning
confidence: 99%
“…There is the also cross-linking method that joining the polymer by another polymer to become like-ladder structures, but this method is not really efficient on shear degradation. The third method which is the most effective method is by the molecular interaction between the polymer and the surfactant [10,11].…”
Section: Introductionmentioning
confidence: 99%